A practical guide to the identification of the coral reef fishes of the tropical central and western Pacific / |c by Robert F. Myers. (Barrigada, Territory of Guam, U.S.A.)
This field guide species. The best guide to the fishes of this region available.
Keywords: Fishes; Identification; Central Pacific Basin